Mathematical Prediction to Combat COVID-19 in Bangladesh by Minimizing the Movement Tendency - Kabir, M. Humayun; Gani, M. Osman; Mandal, Sajib; Biswas, M. Haider Ali (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, we propose a seven compartmental model based on ordinary differential equations (ODEs) to understand the importance of non-pharmaceutical interventions and pharmaceutical protocols. The boundedness and non-negativity of solutions of the model are discussed to ensure the feasibility of solutions of the model. To classify epidemic and endemic cases of the model, we determine the basic reproduction number. Local stability analysis of the non-negative equilibria is performed to gather a dependency of all compartmental populations on time. It is inspected that social awareness parameter controls the symptomatic and asymptomatic populations. It is also found that restrictions on public gathering reduce the transmission of novel coronavirus effectively. Furthermore, the recovery of the COVID-19 infected people is significantly increased when proper medication and adequate clinical support are arranged immediately. Finally, numerical results demonstrate that transmission of novel coronavirus can be prevented and regulated in a densely populated country like Bangladesh when COVID-19 health rules are strictly followed and movement of infected people is minimized as non-pharmaceutical strategies. Apart from non-pharmaceutical interference, medication during quarantine and sufficient clinical support play a pivotal role to minimize the demise of COVID-19 infected people once they are infected.